2017
DOI: 10.1111/wrr.12588
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT cells promote skin wound healing by preventing a prolonged neutrophilic inflammatory response

Abstract: The wound-healing process consists of the inflammation, proliferation, and remodeling phases. In chronic wounds, the inflammation phase is prolonged with persistent neutrophil infiltration. The inflammatory response is critically regulated by cytokines and chemokines that are secreted from various immune cells. Recently, we showed that skin wound healing was delayed and the healing process was impaired under conditions lacking invariant natural killer T (iNKT) cells, an innate immune lymphocyte with potent imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…In addition, our study showed that administration of a-mannan accelerated neutrophil elastase synthesis and that treatment with a neutrophil elastase inhibitor led to improvement of the delayed wound healing caused by a-mannan. NETs contain a high concentration of neutrophil elastase (Brinkmann et al, 2004), which causes degradation of tissue matrix and delay of wound healing (Herrick et al, 1997;Takagi et al, 2017;Tanno et al, 2017). Neutrophil elastase is not only one of the NET components but also acts as an inducer of NET formation (Papayannopoulos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study showed that administration of a-mannan accelerated neutrophil elastase synthesis and that treatment with a neutrophil elastase inhibitor led to improvement of the delayed wound healing caused by a-mannan. NETs contain a high concentration of neutrophil elastase (Brinkmann et al, 2004), which causes degradation of tissue matrix and delay of wound healing (Herrick et al, 1997;Takagi et al, 2017;Tanno et al, 2017). Neutrophil elastase is not only one of the NET components but also acts as an inducer of NET formation (Papayannopoulos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of lymphocytes was found to impair the inflammatory response during injury with a consequence of impaired angiogenesis and an increase in metalloproteinase levels [ 24 ]. In addition, several subsets of T-cell [ 25 ], B-cell [ 26 ], Natural Killer (NK)T-cell [ 27 ] and regulatory T-cells [ 28 ] contribute to wound healing ( Table 1 ) ( Figure 1 ).…”
Section: The Dynamic Phases Of Normal Wound Healingmentioning
confidence: 99%
“…Delayed scar formation may be caused by the regulation of cytokine expression (IL-1B, IL-23, IL-17A) released by Vy4 T cells activated through the T cell receptor (TCR) pathway [233]. Invariant natural killer T (iNKT) cells, which have antigenic features of both T cells and NK cells, regulate neutrophil apoptosis by the expression of IFN-γ, which limits the damage caused by the release of neutrophil elastase, which in turn accelerates the wound healing process [234]. The wound healing process is disturbed in neoplastic diseases, where delayed regeneration actions have been observed at every wound healing stage, and monocyte and T cell infiltration were found to be significantly less in cancer cases than in normal controls, which was associated with a local limitation of neovascularization and collagen synthesis [235].…”
Section: Wound Healingmentioning
confidence: 99%